Moral disengagement in gang versus non-Gang delinquents - Dyberg-Tengroth, M.F.W. (2019)
This thesis explores moral disengagement and the proposed concept of discriminant moral disengagement (DMD) in gang versus non-gang delinquents in England. Chapter One introduces moral disengagement and how it pertains to gangs in the United Kingdom, then sets out the aims and the content of this thesis. A systematic review of violence-targeted interventions for gang youth utilising a moral-component is presented. The review exposes the lack of consistent language in the area and the failure of successful violence interventions with moral components to be specialised for a gang population or applied in England, despite increased interest in moral disengagement as a topic (Chapter Two).